Do individual versus illness belief schema differ in the prediction of post-stroke recovery? - Aujla, Navneet; Walker, Marion F.; Sprigg, Nikola; Vedhara, Kavita (SAGE, 2018)
This longitudinal observational study examined how individual versus illness belief schema compare as predictors of post-stroke recovery. Forty-two stroke survivors (mean age=66.9 years/range=29-96 years; 68% male), were involved. The primary outcome, Health-Related Quality of Life (HRQL) was measured using EQ-5D-5L; mood using Patient Health Questionnaire-9; and disability using Nottingham Extended Activities of Daily Living Scale. Stroke Illness Perception Questionnaire-Revised measured illness beliefs. Linear regressions showed that individual illness beliefs significantly explained more of the variance in three-month post-stroke recovery than schema (7.4-22.5% versus 1.9-9.9%). Individual versus illness belief schema predict outcomes differently, but which approach predicts outcomes better remains unclear.